Implementasi Green Accounting dan Prinsip Maqashid Syariah terhadap Kinerja Keuangan UMKM - Dahlia, Dahlia; Arfah, Arfah; Murnidayanti, Scheilla Aprilia; Heriyani, Heriyani; Putra, Dios Nugraha; Prasetio, Primadi (Magister Ilmu Akuntansi Universitas Jambi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving national economic growth, creating employment opportunities, and enhancing community welfare. Despite their importance, many MSMEs still encounter challenges in adopting accounting practices that integrate environmental considerations and Islamic values. This study aims to examine the influence of green accounting implementation and maqashid sharia principles on the financial performance of MSMEs in Jambi City. Using a quantitative approach, data were collected through questionnaires distributed to 80 MSME respondents and analyzed using multiple linear regression. The results indicate that both green accounting and maqashid sharia principles positively and significantly affect MSME financial performance, demonstrating that environmentally responsible and sharia-based accounting practices can enhance business sustainability and competitiveness in today’s modern economy.